Radiological profile in COVID-19 patients during second wave in Nepal Police Hospital: A descriptive cross-sectional study - Thapa, Subash; Shrestha, Bijaya Ram; Pradhan, Deepa Nhuchhe; Ghimire, Nirmal (Grande Medical Journal, 2021)
Introduction: Chest Radiography is a primary tool available in the clinical assessment for chest manifestation in a patient with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. This study was conducted to determine the utility of chest radiography and characterize the spectrum of chest imaging among COVID-19 patients.Methods: We retrospectively reviewed chest radiographs of 370 confirmed COVID-19 patients presenting to Nepal Police Hospital, Kathmandu from 5 May to 20 June, 2021. The pattern of chest radiography was interpreted and the radiography findings were analyzed based on Modified Chest X-ray scoring system to enhance clinical understanding and prompt assessment of the COVID-19 patients. Pearson’s correlation analysis was used to establish the linear correlation between clinical severity and the Modified Chest X-ray severity score.Result: Out of 370 confirmed COVID-19 patients, 246 patients (66.49%) were male and 124 patients (33.51%) were female. 185 (50%) patients were admitted from the emergency where 154 (83.24%) patients among 185 patients were discharged after recovery whereas 31 patients (24 male and 7 female) died. 229 patients in the study showed normal chest X-ray findings. Among 141 patients with abnormal chest radiography, 121 patients (85.81 %) showed bilateral lung involvement with predominantly ground glass opacity and more on peripheral distribution. Lower zone involvement was the most common findings followed by middle zone involvement. On Modified Chest X-ray severity score, 35.46% were mild, 47.51% were moderate and 17.03% were severe. The scoring showed a moderate positive correlation with the clinical severity of the patient.Conclusions: Chest radiography pattern and scoring system can be used as tools to predict the disease severity in COVID-19 infection. Chest radiography in conjunction with clinical judgment can enhance specific treatment strategies in COVID-19 infection.